1986
DOI: 10.1097/00000658-198612000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function in Women After Proctocolectomy

Abstract: One hundred women who had undergone proctocolectomy with a continence-preserving procedure (50 Kock pouches, 50 ileoanal anastomoses) for ulcerative colitis or polyposis coli were interviewed regarding their preoperative and postoperative sexual function. Frequency of intercourse increased and the incidence of dyspareunia decreased after operation in both groups. Patients who had a Kock pouch had a greater incidence of persistent postoperative dyspareunia than patients who underwent an ileoanal procedure (38% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(46 citation statements)
references
References 11 publications
0
46
0
Order By: Relevance
“…Proctocolectomy and restoration of well-being has been associated with improved sexual function. 20,21 Half of the patients in this study reported no change in libido after surgery, and a quarter reported some improvement. Of the 19% who reported some postoperative restriction of sexual activity, most were women, and this may merit preoperative counseling.…”
Section: Discussionmentioning
confidence: 71%
“…Proctocolectomy and restoration of well-being has been associated with improved sexual function. 20,21 Half of the patients in this study reported no change in libido after surgery, and a quarter reported some improvement. Of the 19% who reported some postoperative restriction of sexual activity, most were women, and this may merit preoperative counseling.…”
Section: Discussionmentioning
confidence: 71%
“…IPAA operation does not jeopardise pregnancy and childbirth but some reports have suggested that it could impair fertility [154,[227][228][229][230][231][232][233]. However, until recently, knowledge about the fertility of women suffering from FAP was sparse and inconclusive [225,234].…”
Section: Fertilitymentioning
confidence: 99%
“…Given that the majority of patients who develop FAP do so either during or before their prime reproductive years, the impact of IPAA on urinary and sexual function in men and women is a most important consideration [4,6,229,247].…”
Section: Urinary and Sexual Functionmentioning
confidence: 99%
“…Impotence and retrograde ejaculation reported after IPAA has only been 1-3 %. More commonly seen is dyspareunia in females and stool leakage during intercourse [ 40 ].…”
Section: Treatment Surgicalmentioning
confidence: 99%